2016
DOI: 10.1128/mmbr.00063-15
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Exploit Viral Entry Routes for Cargo Delivery

Abstract: SUMMARYExtracellular vesicles (EVs) have emerged as crucial mediators of intercellular communication, being involved in a wide array of key biological processes. Eukaryotic cells, and also bacteria, actively release heterogeneous subtypes of EVs into the extracellular space, where their contents reflect their (sub)cellular origin and the physiologic state of the parent cell. Within the past 20 years, presumed subtypes of EVs have been given a rather confusing diversity of names, including exosomes, microvesicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
193
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(206 citation statements)
references
References 183 publications
(241 reference statements)
3
193
0
2
Order By: Relevance
“…Co-localisation studies and assays employing pathway-specific inhibitors revealed involvement of both clathrin-dependent and clathrin-independent endocytosis, including caveolin-mediated endocytosis, macropinocytosis and phagocytosis [22]. These observations seem compatible with receptor-mediated EV uptake mechanisms, similar as for many enveloped viruses [29,30]. To date only few specific cellular receptors for EVs have been proposed.…”
Section: Introductionmentioning
confidence: 86%
“…Co-localisation studies and assays employing pathway-specific inhibitors revealed involvement of both clathrin-dependent and clathrin-independent endocytosis, including caveolin-mediated endocytosis, macropinocytosis and phagocytosis [22]. These observations seem compatible with receptor-mediated EV uptake mechanisms, similar as for many enveloped viruses [29,30]. To date only few specific cellular receptors for EVs have been proposed.…”
Section: Introductionmentioning
confidence: 86%
“…The upregulation of various host molecules derived from exosomes (i.e., CD81, CD63, and CD9) by several viruses and incorporation into the viral membrane for various purposes have been previously described (Dongen et al, 2016). For example, CD63 upregulation during HIV-1 infection has been suggested to mediate CD63 integration into HIV-1 membranes to aid in both viral fusion and replication (Li et al, 2011(Li et al, , 2014Narayanan et al, 2013;Fu et al, 2015;Sampey et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For the purposes of this review, we will focus our discussion on exosomes; however, there are several excellent reviews in the literature that address Electronic supplementary material The online version of this article (doi:10.1007/s13311-016-0450-6) contains supplementary material, which is available to authorized users. extracellular vesicles as a whole [6][7][8][9][10][11]. In appearance, exosomes are unilamellar vesicles composed of a lipid bilayer that have a homogenous cup-shaped appearance on scanning electromicroscopy [3,12].…”
Section: Introductionmentioning
confidence: 99%